Establishment of Chinese Historical Physical Geography: A Comparative Perspective between China and the Soviet Union - Li Dahai (Redai dili, 2025)
Historical physical geography is a discipline that investigates the changes in various natural factors within geographical environments during historical human periods. The establishment of modern Chinese historical geography was profoundly influenced by Western historical geography theories and methodologies, particularly those of the Anglo-Americans. However, the English-speaking academic world lacks a distinct disciplinary framework analogous to that of "historical physical geography" (such as the term "historical physical geography" itself remains exceptionally rare). This discrepancy relates to the fact that historical physical geography, a crucial component and subfield of Chinese historical geography, originated from knowledge exchanges with Soviet theoretical frameworks in the early 1950s. The organizational model of "task-driven disciplinary development" fundamentally catalyzed the establishment of historical physical geography in China and significantly accelerated the modern transformation of Chinese historical geography. While domestic academia has robustly defended the legitimacy of historical physical geography through arguments addressing institutional structures, disciplinary alignment between geography and historical geography, essential differences between natural and human geography research paradigms, and the richness of Chinese historical archives, it remains undeniable that the disciplinary orientation that emerged in the 1950s directly adopted Soviet conceptual frameworks and theories. Furthermore, an academic approach that overlooks the practical realities of Soviet historical geography while seeking to ground the theoretical essence solely within the Chinese context necessitates potential revision and deeper exploration. This study examines the core theoretical contributions of Soviet historical geography during the same period. A comparative analysis of Sino-Soviet developments in historical physical geography reveals that China's "task-driven disciplinary development" model served as the practical foundation for its establishment. Despite direct conceptual influences from Soviet scholarship, Chinese historical physical geography has independently shaped its theoretical framework under specific historical conditions, largely achieving innovation and constructing an autonomous knowledge system, thereby advancing the discipline's comprehensive modernization. As a product of the Sino-Western intellectual synthesis, reconstructing the evolution of Chinese historical geography using a country-specific comparative approach holds significant methodological value in research on the geography of scientific knowledge.